Fisiología del tracto urinario inferior - Valdevenito S., Juan Pablo; Moreno V., Ana María; Salinas C., Pablo; Gómez G., Álvaro; Cuevas T., Miguel Ángel; Díaz L., José Pablo; Vega A., Andrés (Revista Hospital Clínico Universidad de Chile, 2013)
The lower urinary tract has two functional units: a reservoir (the bladder) and an outlet tract (bladder neck, urethra and external urethral sphincter). It is innervated by the sympathetic, parasympathetic and somatic nervous system (NS). During urine storage the bladder is relaxed and the outlet tract contracted (due to an activated sympathetic NS, an inhibited parasympathetic NS and an activation of the somatic NS with increased external urethral sphincter tone and voluntary control of it). During urine emptying the bladder is contracted and the outlet tract relaxed (due to a voluntary relaxation of the external urethral sphincter and an activation of the parasympathetic NS). This operation is controlled by a complex supraspinal neural network systematized in three circuits constituted by the midbrain periaqueductal gray matter and pontine structures, the limbic system and the cortical and cingulated system, which allow the micturition reflex to be mechanically appropriate, emotionally safe and socially appropriate respectively. The knowledge of normal physiology and of the anatomical location of nervous system pathology allows us to infer most of the secondary voiding dysfunctions.